Scientific Writing Series: Design and publication of case reports and case series - Quispe, Antonio M. (2021)
Background: Case reports and case series are essential sources of knowledge; however, they only provide low-quality scientific evidence. These studies are common in the medical field because they allow to formulate new hypotheses and to report new and rare pathologies in a structured way and complications or adverse drug events. Hence, the primary objective of a case report or case series is contributing to the scientific knowledge. To publishing these studies, it is recommended to follow the CARE statement's recommendations to guarantee a structured report with a minimum of pertinent and relevant information to make a clear and precise interpretation of the findings. This review aims to provide a scientific writing guide for case reports and case series and maximize their publicity in indexed peer-reviewed journals.